Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1523/jneurosci.0094-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Arkypallidal and Prototypical Neurons for Phase Transitions in the External Pallidum

Abstract: The external pallidum (GPe) plays a central role for basal ganglia functions and dynamics and, consequently, has been included in most computational studies of the basal ganglia. These studies considered the GPe as a homogeneous neural population. However, experimental studies have shown that the GPe contains at least two distinct cell types (prototypical and arkypallidal cells). In this work, we provide in silico insight into how pallidal heterogeneity modulates dynamic regimes inside the GPe and how they aff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…To do so, we leverage mean-field theory to examine the dynamics of spiking neural networks by making use of a recently developed mean-field theory for networks of coupled spiking neurons with distributed parameters [19,20]. This theory has been used to examine how neural population dynamics change based on cell-intrinsic properties [21,22], coupling between populations [23][24][25], and mechanisms such as gap junction coupling and synaptic plasticity [26][27][28]. Here, we characterize the distinct contributions of within-type and between-type heterogeneity by adapting the mean-field theory to the case of coupled networks containing distinct functional cell types.…”
Section: The Study Of Neural Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…To do so, we leverage mean-field theory to examine the dynamics of spiking neural networks by making use of a recently developed mean-field theory for networks of coupled spiking neurons with distributed parameters [19,20]. This theory has been used to examine how neural population dynamics change based on cell-intrinsic properties [21,22], coupling between populations [23][24][25], and mechanisms such as gap junction coupling and synaptic plasticity [26][27][28]. Here, we characterize the distinct contributions of within-type and between-type heterogeneity by adapting the mean-field theory to the case of coupled networks containing distinct functional cell types.…”
Section: The Study Of Neural Heterogeneitymentioning
confidence: 99%
“…We next investigated the effect of "within-type" heterogeneity on the dynamics of a population of inhibitory neurons, using a model of fast-spiking inhibitory interneurons [29]. Recurrent inhibitory populations are known to exhibit synchronized oscillations given sufficient excitatory drive [15,21]; here we examined how the transition from asynchronous dynamics to synchronous oscillations is affected by spike-threshold heterogeneity (∆ v ).…”
Section: Mean-field Dynamics Of Heterogeneous Fast-spiking Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are significant differences in mutual inhibition in heterogeneous GPe [44,52], whose changes act to produce a series of alterations in the network. Previous studies have found that altered mutual inhibition within GPe generates and regulates its 𝛽 oscillations [38,39] (Fig. 3E).…”
Section: Mutual Inhibitions Between Gpe Are Sufficient To Produce 𝛽mentioning
confidence: 73%
“…This type of gamma-kernel convolution is a popular model for delay-coupled systems with distributed delays [44]. For example, it has been used in [16] to couple populations of neurons via distributed delays that arise from differences in the structure of the neurons and their connections. The following set of code implements a network of N = 5 coupled leaky integrators in RectiPy, with random coupling weights and gamma kernel parameters as given by eqs.…”
Section: 3mentioning
confidence: 99%